Planning in Britain : understanding and evaluating the post-war system - Gilg, Andrew W. (SAGE, 2005)
This accessible textbook offers the first critical introduction to the UK's urban and rural planning policy. Andrew Gilg explains and evaluates policy development at each of the key stages:. · Objectives: what is the aim of planning in the UK?. · Methods: how appropriate is UK planning legislation?. · Procedures: how effective are the planning organizations and processes?. · Impacts: to what extent have planning policies addressed planning problems?. Teaching devices and case studies are used throughout to illustrate the planning process. The text concludes with a discussion of the measurement.